Persistence of Bactericidal Activity at 4 Years After 2 Primary Doses of a Recombinant, 4-Component, Meningococcal Serogroup B Vaccine (4CMenB) and Response to a Booster Dose in Adolescents and Young Adults. (4th October 2017) - Nolan, Terry; Garfield, Hartley; Gupta, Anil; Ferguson, Murdo; Marshall, Helen; D'Agostino, Diego; Toneatto, Daniela
Abstract: Background: This phase 3b, open label, controlled, multi-center, extension study (NCT02446743) assessed the persistence of bactericidal activity at 4 years post-primary vaccination with a recombinant, 4-component, meningococcal serogroup B vaccine (4CMenB) in adolescents who participated in the parent study NCT01423084 and their response to a booster dose, compared with that in vaccine-naïve healthy controls. Methods: Adolescents and young adults previously primed with 4CMenB (2 doses; following a 0, 1-month schedule) in study NCT01423084 (group 3B) and vaccine-naïve 15–22 year olds (group B0_1) were enrolled. Group 3B received a booster dose of 4CMenB at 4 years post-primary vaccination; group B0_1 received 2 catch-up doses of 4CMenB (following a 0, 1-month schedule). Antibody persistence (primary objective) was evaluated at 4 years post-primary vaccination (in group 3B) vs. baseline (in group B0_1) using human serum bactericidal assay (hSBA), in terms of geometric mean titer (GMT) and percentage (%) of individuals with hSBA titer at least 4. Immune responses at 1 month after booster dose (in group 3B) vs. those at 1 month after first dose (in group B0_1) were also assessed. Results: In group 3B, antibody levels declined from 1 month to 4 years post-primary vaccination against all antigens except NHBA, but were higher than in group B0_1 at baseline (Table), with a GMT ratio ≥1.3 and a difference in % of individuals with hSBA titer at least 4 of ≥9%. After one dose of 4CMenB (booster in 3B or first dose in B0_1), GMTs increased (≥4.6-fold in group 3B; ≥2.3-fold in group B0_1), and ≥94% of participants in group 3B and ≥41% of participants in group B0_1 had hSBA titer at least 4 (Table). Conclusion: Antibody levels in adolescents and young adults primed with 4CMenB waned over time but were higher at 4 years post-primary vaccination than for vaccine-naïve individuals at baseline. A booster dose of 4CMenB in vaccine-primed individuals elicited higher immune responses than one dose of 4CMenB in vaccine-naïve individuals. The research was supported by GlaxoSmithKline Biologicals SA. Disclosures: T. Nolan, GSK group of companies: Research Contractor and Scientific Advisor, Research grant. Pfizer: Research Contractor, Research grant. H. Garfield, Novartis/GSK group of companies: Investigator, Research support. A. Gupta, Novartis/GSK group of companies: Investigator, payment for research-related activities; M. Ferguson, GSK group of companies: Investigator, I receive salary from CRG. CRG has contracts with GSK. H. Marshall, GSK group of companies: Grant Investigator and Investigator, Research grant. Pfizer: Grant Investigator and Investigator, Research grant; sanofi pasteur: Grant Investigator, Research grant. Novavax: Investigator, Research grant. D. D'Agostino, GSK group of companies: Consultant, Consulting fee. D. Toneatto, GSK group of companies: Employee, Salary.